The views and experiences of patients and health‐care professionals on the disclosure of adverse events: A systematic review and qualitative meta‐ethnographic synthesis - Raabia Sattar; Judith Johnson; Rebecca Lawton (Wiley, 2020)
Abstract Objective To synthesize the literature on the views and experiences of patients/family members and health‐care professionals (HCPs) on the disclosure of adverse events. Methods Systematic review of qualitative studies. Searches were conducted in MEDLINE, Embase, PubMed, CINAHL and PsycINFO. Study quality was evaluated using the Critical Appraisal Skills Programme tool. Qualitative data were analysed using a meta‐ethnographic approach, comprising reciprocal syntheses of 'patient' and 'health‐care professional' studies, combined to form a lines‐of‐argument synthesis embodying both perspectives. Results Fifteen studies were included in the final syntheses. The results highlighted that there is a difference in attitudes and expectations between patients and HCPs regarding the disclosure conversation. Patients/family members expressed a need for information, the importance of sincere regret and a promise of improvement. However, HCPs faced several barriers, which hindered appropriate disclosure practices. These included difficulty of disclosure in a blame culture, avoidance of litigation, lack of skills on how to conduct disclosure and inconsistent guidance. A lines‐of‐argument synthesis is presented that identified both the key elements of an ideal disclosure desired by patients and the facilitators for HCPs, which can increase the likelihood of this taking place. Conclusions Although patients/family members and HCPs both advocate disclosure, several barriers prevent HCPs from conducting disclosure effectively. Both groups have different needs for disclosure. To meet patients' requirements, training on disclosure for HCPs and the development of an open, transparent culture within organizations are potential areas for intervention.